Vlachs from the area of Herzegovina in the light of Ottoman defter's from the fifteenth and sixteenth centuries - Czamańska, Ilona (Balcanica Posnaniensia. Acta et studia, 2019)
Defter's are an excellent source for historians, especially in demographic and socio-economic research, they are also very useful in researching the Vlachian communities. Analysis of material contained in Ottoman defter's from the Herzegovina area leads to the following conclusions: 1. In the area of Herzegovina, in the second half of the fifteenth century, Vlachs lived in a mostly nomadic lifestyle. Their number was at least sixty thousand people. 2. In the second half of the fifteenth century, many abandoned villages were recorded. Abandoned villages were gradually settled by migratory Vlachs, which contributed to their change of lifestyle on semi-settled and settled. In 1585, Vlachs - shepherds who were not associated with a village were rare. 3. In the Ottoman state, Vlachs those who lead an nomadic way of living, as well as those living in the Vlachian villages, were tax-favored, paid only a lump grazing tax for the state (a filuria with allowances), and did not pay any benefits to the timar owner. In the event that they served as derbenci's or vojnuc's, they were exempted from all taxes. 4. Settling in the former agricultural villages, in particular related to undertaking agricultural activities, was most often associated with an additional burden of tithing for the sipahi. Departure from pastoralism meant degradation to a group of raya, most often in these villages mixed-agricultural-pastoral management was conducted. Newly settled villages rarely received the status of the vlachian villages, because such status freed residents from additional benefits even in the case of agricultural classes. 5. The flat-rate grazing tax, filuria, in the fifteenth century had a fixed value and equaled 45 akçe, while at the end of the sixteenth century it was different for various Vlachs groups and could range from 60 to 200 akçe. Considering the fact that additional fees for sheep or tents were liquidated and that the value of employment fell akçe significantly compared to the fifteenth century, the real amount of taxes did not increase, and in some cases it decreased. 6. Not much on the basis of defilers can be said about the language used by the Herzegovina Vlachs. In defeats from the fifteenth century they bear mostly Slavic names, but sometimes there are also names only in the Vlachs: Radu, Bratul, Dabija, the same also applies to local names. 7. Gradually, Islamization processes took place. In the fifteenth century, they are almost invisible among the Vlachs, almost all of them wore Christian names. At the end of the sixteenth century, a significant percentage of Vlachs wore Muslim names. The Islamization process seems to be faster among the Vlachs settled than the Vlachs nomads, but there is no rule. 8. In the light of the defters in the area of Herzegovina, there is no difference between Muslims and non-Muslims in burdens to the state, but defters do not include the cizye, or headship, collected from non-Muslims.